Association between stress hyperglycemia ratio and all-cause mortality in critically ill patients with atrial fibrillation: insights from a MIMIC-IV study - Liu, Lin; Zhu, Zhanfang; Yu, Kai; Zhang, Wei; Pu, Jie; Lv, Ying; Tang, Zhiguo; Liu, Fuqiang; Liu, Shasha (Frontiers in Endocrinology, 2024)
The stress hyperglycemia ratio (SHR) has emerged as a potential prognostic indicator for various critical illnesses. However, its role in determining outcomes in patients with atrial fibrillation (AF) within the intensive care unit (ICU) remains unclear. This study aimed to elucidate the association between SHR and all-cause mortality in this clinical setting.We conducted a retrospective cohort study utilizing data from a large, retrospective database. Critically ill patients with documented AF were stratified based on quartiles of SHR. The primary outcome was 365-day all-cause mortality, with secondary outcomes including 90-day and 28-day mortality. COX proportional hazards models adjusted for confounders and Kaplan-Meier curve analyses were used to explore the relationship between SHR and mortality.Results: 2,679 patients with critical AF were enrolled in the final study. Among the patients studied, those in the highest SHR quartiles exhibited an increased risk of 365-day all-cause mortality (HR:1.32, 95%CI=1.06-1.65). Notably, in subgroup analyses, the prognostic value of SHR was particularly pronounced in patients with hypertension. Sensitivity analyses confirmed the persistence of these findings after excluding cohorts with malignant tumors, and heart failure.Our research discerns a positive association between SHR and all-cause mortality in critically ill patients with AF, highlighting the significance of acute glycemic dysregulation on patient outcomes. Longer follow-up is still needed in the future to study the association between SHR and all-cause mortality in critically ill patients with AF.